Electric Voltage Stabilizer for Bread Oven as an Effort to Increase Production in Medan City - Hasugian, Ivo Andika; Nasution, Dian Morfi; Hasibuan, Novrida Harpah; Dewi, Rezky A. (Talenta Publisher, 2022)
Nowadays, business developments are increasingly stringent, even though they are in an economic condition that tends to be unstable due to the impact of the pandemic. This has an impact on business competition that is getting higher and sharper, both in the domestic market and in the international market. Every business in high competition is required to always compete with other companies in the same industry. One way to win the competition or at least survive in the competition is to give full attention to the quality of the products produced by the company and ensure smooth production so that production targets can be achieved. One of the efforts to smooth production is to fix problems that occur in production. The constraint experienced by partners is that the production target is not achieved because the toaster oven stops rotating. Based on the analysis, it was found that this problem was caused by fluctuations in the electric voltage that entered the toaster oven. So based on the survey and discussion conducted by the team, to overcome the problems experienced by partners, the team proposes to design and assemble an Assembled Electrical Voltage Stabilizer for Toaster Ovens. The target and outcome of this activity is to increase the partner's production capacity by using an Electric Voltage Stabilizer.